Developing an impact assessment toolkit for creative sustainable tourism initiatives - Costa, P. (2019)
Creative tourism advocates new experiences for promoters, tourists and communities, as new modes of collaboration, partnership, and organization. Despite being an expanding offer and targeting niche markets, creative tourism is already recognized by the different ways of producing and consuming tourism experiences and for its ability to add value in the territories where they take place. The development of this type of experience in small cities and rural areas not only gives centrality to sustainability issues but also makes it important to observe and discuss the potential impacts of these experiences in this kind of territories. There are few studies that attempt to measure the impacts of creative tourism activities in accordance with the principles of sustainability, or that seek to develop analytical models appropriate to the particular characteristics of small cities and rural areas. Within the scope of the CREATOUR project, we started to develop a theoretical and methodological framework, aiming to propose a more integrated model, recognizing the several dimensions of sustainability and the specificities of the territories involved and taking into account the different actors involved in creative tourism. Based on the data gathered from the CREATOUR pilot initiatives, this communication will present the analysis of the perceptions that the different pilots have about the various effects of the implementation of these exploratory experiences, considering the objectives that they established for their realization. This analysis is useful to reflect on the particularities of this type of exercise and to improve our model. The final goal is to propose a more robust toolkit for impact assessment to be presented to all partners interested in developing or updating their creative tourism projects.